Quiet firing as a form of constructive dismissal: Analysis of normative vacuum and protection of the right to decent work in Indonesian Labor Law - Nadhiva Rizky Budhyarto (PT WIM Solusi Prima, 2026)
Quiet firing has emerged as a salient development in modern employment relations. Unlike conventional termination, quiet firing operates through indirect managerial actions that pressure employees to resign, such as exclusion from work activities, restricted promotions, reduced responsibilities, and sustained psychological pressure. Indonesian labor law does not explicitly recognize or regulate this practice. This normative legal study examines whether quiet firing qualifies as constructive dismissal, explores the regulatory vacuum in Indonesian labor law, and assesses its implications for the right to decent work as a human right. Using statutory, conceptual, and comparative approaches, the study finds that quiet firing substantively meets the characteristics of constructive dismissal by creating objectively unacceptable working conditions that induce resignation. The absence of specific regulation generates legal uncertainty and weakens worker protection, including dignity, fair treatment, career development, and mental health. The article proposes recognizing constructive dismissal as a distinct termination category grounded in the ILO Decent Work Agenda (1999), with clear elements, calibrated burden of proof, and remedies (severance, compensation, reinstatement) within Indonesia’s industrial dispute resolution framework.